The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ppc.12982
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of stigma toward people with mental illness among university and school students

Abstract: Purpose This study aimed to explore the associated factors of stigma towards people with mental illness among Omani school and university students. Design and Method A cross‐sectional study among 371 school and university students with a multivariable linear regression model to identify the associated factors of personal and perceptions of stigma. Results Male students, those with highly educated mothers, have high monthly income, higher mental health knowledge, employed fathers, and received focused education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…This study found that stigma agreement was high among students who had illiterate parents. These findings resonate with previous studies in Oman where the mother's level of education, and family income were significantly associated with mental health stigma (Al Omari et al, 2021). Overall, these findings support the trend revealed in previous research that knowledge and stigma are inversely proportional (Heary et al, 2017;Kaushik et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study found that stigma agreement was high among students who had illiterate parents. These findings resonate with previous studies in Oman where the mother's level of education, and family income were significantly associated with mental health stigma (Al Omari et al, 2021). Overall, these findings support the trend revealed in previous research that knowledge and stigma are inversely proportional (Heary et al, 2017;Kaushik et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence that mental illness is still perceived by most communities worldwide as a character weakness, a punishment for immoral behaviour, the result of illicit drug taking or a result of supernatural forces (Chatterjee & Singh, 2018;Corrigan, 2018;Maier et al, 2014;Seeman et al, 2016). The prevalence of stigma seems to be higher in Arabspeaking countries compared with the rest of the world (Al Omari et al, 2021;Seeman et al, 2016;Shehata & Abdeldaim, 2020). This could be due to insufficient mental health knowledge among university students (Al Omari et al, 2020) and absent or inefficient monitoring mechanisms of mental health legislation and policies within the healthcare setting, as reported by a review of mental illness stigma in the Arab world (Merhej, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the total scores for knowledge and positive attitude toward people with mental illness were low in the current study. Previous research in the Arab region [8,9,11,30] and elsewhere [31] had similar results among students and teachers [21,32]. There is a need to integrate or adopt mental health programmes to refresh and improve teachers' current knowledge about mental illness.…”
Section: Discussionmentioning
confidence: 73%
“…Although the general public's knowledge about mental illness has improved, a negative attitude among Jordanian adolescents remains [8,10]. Gender, level of education, previous mental health training, having a family history with a mental illness, and/or socio-economic status were found to predict stigma among teachers and their students [11,12].…”
Section: Introductionmentioning
confidence: 99%